الحجر في قانون الأسرة الجزائري - - فتيحة بودية (المسيلة, 2023)
يعتبر الحجر في القانون موضوعا بالغ الأهمية، كونه يتعلق بأهلية الاشخاص ،وما يلحقها من عوارض تقف حاجزا بين ممارسة هذه الأهلية،كالجنون والعته والسفه والغفلة،أومانع من موانعها كالمدين المفلس أو المحكوم عليه بعقوبة جنائية. و يتم عن طريق حكم قضائي صادر عن قاضي شؤون الأسرة المختص، فينتج آثارا قانونية تتمثل أساسا في تعيين قيم على المحجور عليه لإدارة أمواله، والقيام مقامه بمقتضى ما هو منصوص عليه قانونا. تكون تصرفات المحجور عليه دائرة بين البطلان التام (المطلق) والبطلان الناقصوعليه فالبطلان يقرر في حالة لم يستطع المحجور عليه ،التمييز بين النفع والضرر بعد الحكم عليه كحالات الجنون والعته، غير أنها تعد ناقصة كتصرفات الصبي المميز ، إذا كانت نافعة تعد صحيحة كقبول التبرعات والهبات،وتكون باطلة بطلانا مطلقا إذا كانت ضارة له ضررا محضا كالتبرع بأمواله،أماإذا كانت دائرة بين النفع والضرر فتكون قابلة للبطلان. تعتبر دعاوى الحجر من النظام العام يتمسك بها كل من له مصلحة ،وللقاضي أن يحكم به من تلقاء نفسه،وينقضي الحجر بنفس إجراءات توقيعه وللقاضي أيضا سلطة الحكم برفعه أو زوال أسبابه وله السلطة التقديرية في كيفية ذلك وفقا للإجراءات المخولة قانونا كالاستعانة بالخبراء . الكلمات المفتاحية: الحجر،العوارض، تصرفات المحجور عليه، دعوى الحجر، رفع الحجر. Abstract Restriction in the law is a very important topic, as it relates to the capacity of persons and the accompanying symptoms that stand as a barrier between the exercise of this capacity, such as insanity, dementia, foolishness and negligence, or one of its impediments, such as a bankrupt debtor or a person sentenced to a criminal penalty. It is done through a judicial ruling issued by the competent family affairs judge; it produces legal effects mainly represented in appointing a trustee of the restricted person to manage his money and act in his place according to what is stipulated in the law. The actions of the restricted person are a circle between the complete (absolute) invalidity and the incomplete invalidity. Accordingly, the invalidity is decided in a case where the restricted person could not distinguish between benefit and harm after being judged, such as cases of insanity and dementia. However, they are considered incomplete, such as the actions of a discerning boy. If they are beneficial, they are considered correct, such as accepting donations. And it is absolutely null and void if it is purely harmful to him, such as donating his money, but if it circles between benefit and harm, then it is subject to nullity. Restriction lawsuits are considered part of the public order, and everyone who has an interest cling to them. The judge may rule on it on his own, and the restriction ends with the same procedures of its signature. The judge also has the authority to rule on its lifting or the demise of its causes, and he has the discretionary power in how to do so in accordance with the procedures authorized by law, such as seeking the assistance of experts. Keywords: Restriction, the behavior of the restricted person, the actions of the restricted person, the filing of the action of the restriction.
Keywords: الحجر،العوارض، تصرفات المحجور عليه، دعوى الحجر، رفع الحجر.